Liquid : a love story - Rahmani, Mariam (Algonquin Books of Chapel Hill, 2025)
"The story of a young Muslim scholar stuck in the mire of adjunct professorship in Los Angeles who decides to give up her career in academia and marry rich, committing herself to one hundred dates in the course of a single summer"--